HOW GLOBAL ARE GLOBAL VALUE CHAINS? A NEW APPROACH TO MEASURE INTERNATIONAL FRAGMENTATION1. (9th April 2014) - Los, Bart; Timmer, Marcel P.; de Vries, Gaaitzen J.; Brakman, Steven; van Marrewijk, Charles; Partridge, Mark
ABSTRACT Denser networks of intermediate input flows between countries suggest ongoing international fragmentation of production chains. But is this process mainly taking place between countries within a region, or is it truly global? We provide new macroeconomic evidence by extending the Feenstra and Hanson (1999) measure of fragmentation to a multicountry setting. We derive the distribution of value added by all countries involved in the production chain of a particular final good. This is based on a new input–output model of the world economy, covering 40 countries and 14 manufacturing product groups. We find that in almost all product chains, the share of value added outside the country‐of‐completion has increased since 1995. This is mainly added outside the region to which the country‐of‐completion belongs, suggesting a transition from regional production systems to "Factory World." This tendency was only briefly interrupted by the financial crisis in 2008.